A qualitative study of patients' perspectives on collaboration to support self-management in routine rheumatology consultations. Issue 1 (December 2016) - Dures, Emma; Hewlett, Sarah; Ambler, Nicholas; Jenkins, Remona; Clarke, Joyce; Gooberman-Hill, Rachael
Abstract Background Self-management of inflammatory arthritis (IA) requires patients to address the impact of symptoms, treatment, and the psychosocial consequences of a long term condition. There are several possible mechanisms for facilitating self-management, including patient-clinician interactions in routine consultations. This requires patients to collaborate in their healthcare, and clinicians to specifically encourage and help patients to do so. To design training that enables clinicians to support patients to be actively involved and self-manage requires understanding both patients' and clinicians' perspectives about what is important and feasible. Previous research explored the perspectives of clinicians who had undertaken brief training which they were putting into practice in their routine consultations. This study explored the perspectives of patients attending those routine consultations to identify aspects of the interaction that influenced collaboration and self-management. Methods Nineteen patients with IA who had attended a routine consultation with a rheumatology clinician at one of four hospitals in England took part in semi-structured interviews. Interviews were transcribed, anonymised and analysed using inductive thematic analysis. Results Three themes encompass participants' thoughts about interactions that facilitated collaboration in consultations and their ability to self-manage their IA: first, patients and clinicians viewing care as a shared endeavour, including patients responding actively to their IA and clinicians exploring and negotiating with patients; second, the need for clinicians to understand the challenges faced by patients, appreciate the impact of IA and focus on patients' priorities; and third, clinicians using an open communication style, including the use of non-didactic, patient-centred approaches. A fourth theme was perceived benefits of actively engaging in consultations, including increased confidence to deal with the impact of IA and greater acceptance of a long term condition. Conclusions Patients perceive that self-management can be facilitated when clinicians and patients view healthcare as a shared responsibility, underpinned by clinicians as experts in the disease and patients as experts in living with it. Clinicians can support patients' self-management by using non-didactic communication skills to identify patients' priorities, and to prompt patients to problem-solve and share in setting the consultation agenda. This should inform skills-training for rheumatology clinicians.